Three-phase smart inverter for flexible power conditioning in low voltage distribution systems - Mortezaei, A. H.; Hou, Xuhang; Snnões, Marcelo G.; Busarello, Tiago Davi Cun; Marafão, Fernando P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
IUs paper presents a three-phase smart inverter able to perform multi-task functionalities in low voltage distribution systems. The primary merit of such a smart inverter is the possibility of allowing flexible power conditioning in grid following mode and establishing regulated output voltage for critical loads in grid forming mode (islanded operation). Therefore, it is possible to inject active power plus compensate unwanted current terms (reactive, unbalance, and distortion), enabling full exploitation of the smart inverter capability and increasing its overall cost-benefit and efficiency. Furthermore, mitigating the electrical disturbances from the load currents improves the power quality for utility enhanced performance. Two well-known power theories, namely Conservative Power Theory (CPT) and Instantaneous Power theory (PQ) were considered from the performance perspective in multi-task operation. This may be particularly important for defining technical responsibilities in smart microgrids or in modern power grids. This paper also proposes the analysis and design of a cascaded voltage control scheme based on an inductor current feedback and load current feed-forward strategy for regulating and establishing the three-phase output voltage for critical loads. The principles supporting the developed control strategy are discussed and experimental results are provided in order to show the performance and robustness of the proposed control strategies.
Keywords: Conservative Power Theory (CPT); Digital control; Distributed generation (DG); Instantaneous Power theory (PQ); Microgrid; Power quality improvement